2020
DOI: 10.1155/2020/8812277
|View full text |Cite
|
Sign up to set email alerts
|

Stability Analysis of a Two‐Layered Slope with Cracks by Finite Element Limit Analysis

Abstract: In this study, to support slope stability estimating engineering, the stability of a slope with cracks lying on two-layered slopes was investigated by a self-developed adaptive element limit analysis (AFELA) code. Upper bound (UB) and lower bound (LB) results of soil additional gravity factor SF within 4% relative error were obtained to quantify the effects of several factors, including the Moore‒Cullen strength ratio, angle of the slope, thickness of the top layer, length of the crack, angle of the crack, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
1
1
0
Order By: Relevance
“…Although present numerical results are discussed in view of the magnitude and location of CSRF and the size of the failure zone, further study will be interesting to correlate them. Finally, it would also be interesting to carry out a three-dimensional analysis of a rock slope in the presence of both tension cracks and joints [23,[29][30][31]. The present numerical study establishes that failure of the rock slope in the presence of an inclined TC results in a change of both magnitude and location of the Critical Strength Reduction Factor.…”
Section: Effect Of Distance Of a Tc From Crest On Csrfsupporting
confidence: 59%
See 1 more Smart Citation
“…Although present numerical results are discussed in view of the magnitude and location of CSRF and the size of the failure zone, further study will be interesting to correlate them. Finally, it would also be interesting to carry out a three-dimensional analysis of a rock slope in the presence of both tension cracks and joints [23,[29][30][31]. The present numerical study establishes that failure of the rock slope in the presence of an inclined TC results in a change of both magnitude and location of the Critical Strength Reduction Factor.…”
Section: Effect Of Distance Of a Tc From Crest On Csrfsupporting
confidence: 59%
“…Studies have shown that although the magnitude of CSRF changes linearly with cohesion and angle of internal friction of slope rock mass, the location of CSRF does not depend on it [28,29]. In the present study, the effect of an inclined tension crack on CSRF is investigated numerically as a function of inclination angle and crest distance of TC [30,31]. Further, TC is replaced with a joint to examine the effect of a sloping mass on CSRF/FoS.…”
Section: Introductionmentioning
confidence: 87%